2015
DOI: 10.5336/anesthe.2014-42788
|View full text |Cite
|
Sign up to set email alerts
|

Our Experiences with Spinal Anesthesia in 143 Pediatric Patients

Abstract: Ö ÖZ ZE ET T AAm ma aç ç: : Spinal anestezi, erişkinlerde olduğu kadar çocuklarda da popularitesi artan bir tekniktir. Hızlı başlangıçlı sensöriyel blok ve tam bir kas gevşemesi sağlaması, aynı zamanda cerrahiye stres yanıtın ve kardiyovasküler yanıtın da kontrol edilebilmesi nedeni ile çocuk cerrahisinde popularitesini artırmıştır. Bu çalışmanın amacı, spinal anestezi uyguladığımız hastalarda bu tekniğin etkinliğini, yan etkilerini ve komplikasyonlarını geriye dönük olarak değerlendirmektir. G Ge er re eç ç v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
(20 reference statements)
0
0
0
Order By: Relevance
“…Caliskan et al 12 reported mild headache not fully compatible with PDPH criteria in one case (1.1%). Kantekin et al 13 encountered no PDPH in their study. No PDPH was also observed in the present research, and this is also consistent with the literature and other studies from Türkiye.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Caliskan et al 12 reported mild headache not fully compatible with PDPH criteria in one case (1.1%). Kantekin et al 13 encountered no PDPH in their study. No PDPH was also observed in the present research, and this is also consistent with the literature and other studies from Türkiye.…”
Section: Discussionmentioning
confidence: 81%
“…Remifentanil infusion was initiated as an additional anesthetic agent for maintenance of anesthesia in 13.6% of patients with laryngeal masks. Figures of 35% were reported by Caliskan et al 12 17.4% by Kantekin et al 13 and 22% by Baltrak and Soyalp. 14 The figure for supplemental anesthesia in this study was thus slightly lower than in other research from Türkiye.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation